PERANAN KUALITAS PELAYANAN, HARGA DAN KELENGKAPAN PRODUK dalam meningkatkan LOYALITAS KONSUMEN DI UNIMUS MART SEMARANG - Astono, Ari Dwi; Suharti; Dwi Atmini , Ninik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Indonesia's economic development is increasing and entrepreneurs compete with each other in business. Unimus mart is a business unit of the Muhammadiyah University of Semarang whose business activities have received interesting attention. The aim of this research is to test Service Quality (X1), Price (X2) and Product Completeness (X3) and Consumer Loyalty (Y) at Unimus mart Semarang. The research population is Unimus mart consumers who have made at least 2 purchases, the number of which is unknown, while the sample was calculated using the Lemeshow formula of 100 respondents. The sampling technique was accidental sampling technique. Data analysis uses multiple linear regression. The results of this research show that price has a positive and significant influence on consumer loyalty. Product completeness has no effect on consumer loyalty. Service quality has a positive and significant effect on consumer loyalty. And simultaneously price, product completeness and service quality have a positive and significant effect on consumer loyalty.